Examining Canonisation in Modern African Literature - Ojaide, University of North Carolina-Charlotte, USA, Tanure (Asiatic: IIUM Journal of English Language and Literature, 2009)
This essay examines the idea of an African literary canon through the creative works of African writers, their criticism by African literary scholars, and the validation of African aesthetic values. Based on the premise that literature is a cultural production, modern African literature expresses the socio-cultural, historical, and other experiences as well as the sensibility of its people. Literary works that focus on certain criteria of cultural acceptability, African-ness, or Africanity constitute modern African literature and its canon. Since modern African literature is still relatively young compared to Western literatures, there have been debates and controversies over what is truly African literature. It is in the context of the peopleâ€™s overall experience and the aesthetic considerations involved that canonisation will be discussed. Among these issues are the language of modern African literature and the current debate as to whether African writers in the West (North America and Europe) writing and publishing there are still African writers. Cultural identity and what constitutes what Abiola Irele describes as â€œthe African imaginationâ€ will thus be the touchstones of any African literary canon. As a result of the postcolonial experience shared by many African and Asian societies, many of the issues relating to African literature and its canon will likely have parallel responses in modern Asian literary discourse. Â